The African swine fever virus protease pS273R inhibits DNA sensing cGAS-STING pathway by targeting IKKε. Issue 1 (31st December 2022) - Luo, Jia; Zhang, Jiajia; Ni, Jinghua; Jiang, Sen; Xia, Nengwen; Guo, Yiwen; Shao, Qi; Cao, Qi; Zheng, Wanglong; Chen, Nanhua; Zhang, Quan; Chen, Hongjun; et al.
ABSTRACT: African swine fever virus (ASFV), a large and complex cytoplasmic double-stranded DNA virus, has developed multiple strategies to evade the antiviral innate immune responses. Cytosolic DNA arising from invading ASFV is mainly detected by the cyclic GMP-AMP synthase (cGAS) and then triggers a series of innate immune responses to prevent virus invasion. However, the immune escape mechanism of ASFV remains to be fully clarified. The pS273R of ASFV is a member of the SUMO-1-specific protease family and is crucial for valid virus replication. In this study, we identified pS273R as a suppressor of cGAS-STING pathway mediated type I interferon (IFN) production by ASFV genomic open reading frame screening. The pS273R was further confirmed as an inhibitor of IFN production as well as its downstream antiviral genes in cGAS-STING pathway. Mechanistically, pS273R greatly decreased the cGAS-STING signaling by targeting IKKε but not TBK1, and pS273R was found to disturb the interaction between IKKε and STING through its interaction with IKKε. Further, mutational analyses revealed that pS273R antagonized the cGAS-STING pathway by enzyme catalytic activity, which might affect the IKKε sumoylation state required for the interaction with STING. In summary, our results revealed for the first time that pS273R acts as an obvious negative regulator of cGAS-STING pathway by targeting IKKε via its enzymatic activity, which shows a new immune evasion mechanism of ASFV.